Study On Functional Facilities Utilization Of Bungus Fishing Port At West Sumatera Province - Zain, Jonny; ', Nurholis; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The Purpose of this study is to know the functional facilities utilization of Bungus fishing port. A series survey was conducted in October 1th-11th 2013. Based on survey result revealed that functional facilities there is tuna processing building, dry ice building, net repairing loft, fish market hall, fresh water tank, fuel tank and ice factory. From 8 facilities existing, only 3 facilities that could be analyzed. Based on analyzed, it is found that the utilization rate of fuel tank is 38.31% were classified not good, fresh water tank at 30.53%, which is still classified not good, and the ice factory was 65.91% were classified as less better.Keywords: fishing port, functional facilities, utilization level